2018
DOI: 10.1172/jci121525
|View full text |Cite
|
Sign up to set email alerts
|

Active suppression rather than ignorance: tolerance to abacavir-induced HLA-B*57:01 peptide repertoire alteration

Abstract: The discovery of HLA-B*57:01-associated abacavir hypersensitivity is a translational success story that eliminated adverse reactions to abacavir through pretreatment screening and defined a mechanistic model of an altered peptide repertoire. In this issue of the JCI, Cardone et al. have developed an HLA-B*57:01-transgenic mouse model and demonstrated that CD4+ T cells play a key role in mediating tolerance to the dramatically altered endogenous peptide repertoire induced by abacavir and postulate a known mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
(21 reference statements)
1
9
1
Order By: Relevance
“…Our results are consistent with the earlier reports 14,18,19 that CD8 and not CD4 T cells are responsible for abacavir‐induced immune response in HLA‐B*57:01 pos ABH pos individuals. It has also been hypothesized that CD4 T cells contribute to the tolerance of abacavir in HLA‐B*5701 patients, leading to the high number of false positives through HLA screening 22 . On the contrary, our study showed that both CD4 and CD8 T cells showed similar immune response when stimulated with SEB, though as expected, SEB‐specific CD8 T cells were more degranulating while CD4 T cells were more cytokine producing.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our results are consistent with the earlier reports 14,18,19 that CD8 and not CD4 T cells are responsible for abacavir‐induced immune response in HLA‐B*57:01 pos ABH pos individuals. It has also been hypothesized that CD4 T cells contribute to the tolerance of abacavir in HLA‐B*5701 patients, leading to the high number of false positives through HLA screening 22 . On the contrary, our study showed that both CD4 and CD8 T cells showed similar immune response when stimulated with SEB, though as expected, SEB‐specific CD8 T cells were more degranulating while CD4 T cells were more cytokine producing.…”
Section: Discussionsupporting
confidence: 85%
“…It has also been hypothesized that CD4 T cells contribute to the tolerance of abacavir in HLA-B*5701 patients, leading to the high number of false positives through HLA screening. 22 On the contrary, our study showed that as well as those of CFSE low CD4 and CD8 T cells (plot d). Significance of the difference between different groups is given in the upper section of the plots both CD4 and CD8 T cells showed similar immune response when stimulated with SEB, though as expected, SEB-specific CD8 T cells were more degranulating while CD4 T cells were more cytokine producing.…”
Section: Discussioncontrasting
confidence: 53%
“…Hence, some who carry the HLA-B*57:01 allele do not have adverse drug reactions to abacavir. This discovery also allows for future studies in the field of T-cell-mediated drug tolerance [2].…”
Section: Pharmacogenomicsmentioning
confidence: 91%
“…CD28 costimulation promotes T cell proliferation, cytokine production, and T cell survival (74). In a transgenic mouse model for HLA-B*57:01linked abacavir hypersensitivity, CD80 on DCs are upregulated upon CD4+ T cell depletion (likely including Tregs), resulting in an adverse immune response (52,53). To further assess the effect of blocking this pathway on DTH, mice with antibodies targeting CD28 or CD80 inhibited the accumulation of reactive CD8+PD-1+ T cells in the lymph nodes, dampening the immune response to abacavir.…”
Section: Cd28mentioning
confidence: 99%